Dore after London - Wayne Michael Charney (Oz, 1989)
There was, perhaps, no other city in the world so thoroughly studied, chronicled, and recorded in 19th-century literature and art than was the city London. Charming, picturesque descriptions of London from the first half of the century eventually gave way to more sober and unattractive views by the 1860s.